Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004075.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fetal pulse oximetry for fetal assessment in labour

Abstract: Background Pulse oximetry could contribute to the evaluation of fetal well-being during labour. Objectives To compare the effectiveness and safety of fetal pulse oximetry with conventional surveillance techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…East et al have reported that during the active phase of labor, every method has a significant rate of signal loss and the loss of sensor contact occurred up to 64% of time with oximetry. 6 Another drawback of this transvaginal procedure is that the probe often moves away from the fetal head during delivery, which may lead to an intrauterine infection caused by rupture of the gestational sac. Furthermore, these methods are essentially invasive, as the probe is inserted into the uterine cervix only after the rupture of the gestational sac.…”
Section: Introductionmentioning
confidence: 99%
“…East et al have reported that during the active phase of labor, every method has a significant rate of signal loss and the loss of sensor contact occurred up to 64% of time with oximetry. 6 Another drawback of this transvaginal procedure is that the probe often moves away from the fetal head during delivery, which may lead to an intrauterine infection caused by rupture of the gestational sac. Furthermore, these methods are essentially invasive, as the probe is inserted into the uterine cervix only after the rupture of the gestational sac.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies with conflicting findings on the predictive value of SpO 2 in adult and pediatric populations. [4][5][6][7][8][9] While there are limited data related to a normal range in pregnancy against which to measure physiological perturbations, a suggested normal value for SpO 2 in pregnancy is ≥ 97%. 10 The ability of maternal SpO 2 to predict adverse maternal outcomes has been poorly studied, and in the few studies of the subject the definitions of oxygen desaturation events are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal pulse oximetry was developed in the 1990s, but the commercialization of electrodes has subsequently been discontinued. A systematic review of four trials comparing CTG + fetal pulse oximetry with isolated CTG showed no difference in the overall cesarean delivery rate (relative risk [RR] 0.99; 95% CI, 0.86-1.13), while adverse fetal outcomes were rare in both groups [4]. The present chapter focuses on the adjunctive technologies currently available for intrapartum fetal monitoring.…”
Section: Introductionmentioning
confidence: 96%